2004
DOI: 10.2337/diabetes.53.12.3097
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 1

Abstract: Obesity, with its related problems, is recognized as the fastest growing disease epidemic facing the world, yet we still have limited insight into the regulation of adipose tissue mass in humans. We have previously shown that adipose-derived microvascular endothelial cells (MVECs) secrete a factor(s) that increases proliferation of human preadipocytes. We now demonstrate that coculture of human preadipocytes with MVECs significantly increases preadipocyte differentiation, evidenced by dramatically increased tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
116
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 45 publications
6
116
1
1
Order By: Relevance
“…Inhibition of FGFR activation during proliferation decreased FGF1 priming and differentiation potential of human PA [29]. This priming effect of preadipocytes was more apparent if the cells were differentiated exposed to a PPAR-γ ligand [27]. Jonker et al also verified that FGF1 was a direct target of PPARγ in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Inhibition of FGFR activation during proliferation decreased FGF1 priming and differentiation potential of human PA [29]. This priming effect of preadipocytes was more apparent if the cells were differentiated exposed to a PPAR-γ ligand [27]. Jonker et al also verified that FGF1 was a direct target of PPARγ in HFD-fed mice.…”
Section: Discussionmentioning
confidence: 63%
“…Subjects in the upper serum FGF1 tertile had higher levels of BMI, [17]. So far, mounting evidence from previous studies highlighted an essential role of FGF1 in proliferation and differentiation of primary human preadipocytes (phPA) [23,27]. Louise et al showed that the proliferation rate of phPA was increased in the presence of FGF1, and this effect can be blocked by addition of a neutralizing antibody raised against FGF1 [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kiseli fibroblastni faktor rasta (aFGF-1) i bazni fibroblastni faktor rasta (bFGF-2) identifikovani su u fluidu rane, naročito u najranijim fazama zarastanja 41 . Uloga FGF u zarastanju rane je dokazana in vitro i in vivo kroz akciju u ranoj aktivaciji makrofaga, povećanju komponenti ekstracelularnog matriksa, povećanju proliferacije i diferencijacije neuroektodermalnih i mezodermalnih derivata, endotelnoj ćelijskoj proliferaciji, adipogenezi, angiogenezi i reepitelizaciji 42,43 . Najveću ulogu u procesu zarastanja rane ima kiseli fibroblastni faktor rasta (aFGF-1) koji utiče na proliferaciju fibroblasta i endotela, promovišući zarastanje rane i angiogenezu.…”
Section: Fibroblastni Faktori Rastaunclassified
“…Treatment of endothelial cells with FGF1 causes microvascular branching, suggesting a possible role in angiogenesis [8]. Intriguingly, as a proliferative factor, FGF1 may also play an important role in adipogenesis [9]. Due to its beneficial impact on the circulatory system, FGF1 has been tested for clinical applications in cardiovascular diseases npg [7].…”
mentioning
confidence: 99%